ANALYSIS OF ZAKAT ACCOUNTING TREATMENT BASED ON PSAK NO.109 IN MEASURING TRANSPARENCY AND ACCOUNTABILITY IN ZAKAT AML INSTITUTIONS YATIM MANDIRI MEDAN - Sri Fitria Jayusman; Ricka Putri; Munawaroh; Melisa Zuriani Hasibuan; Horia Siregar; Toni Hidayat (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This research aims to analyze the zakat accounting treatment implemented by the Amil Zakat Yatim Mandiri Medan Institute and whether it is in accordance with PSAK No.109. Apart from that, the aim of this research is to analyze transparency and accountability in the presentation of financial reports implemented by the Amil Zakat Yatim Mandiri Medan Institute. The research method used is a qualitative method with descriptive analysis using primary data taken from financial report data and the interview method. The results of the research concluded that the Amil Zakat Yatim Mandiri Medan Institution in its zakat accounting treatment was in accordance with PSAK No.109 whichseen from the financial position report data which separates zakat, infaq/alms funds and non-zakat, infaq/alms funds in the financial position report. The accountability measurements carried out by the Amil Zakat Yatim Mandiri Medan Institution in presenting and distributing financial reports are in accordance with the performance indicators of the Medan Amil Zakat Yatim Mandiri Institution in distributing funds, as well as indicators of financial reports that have been published and carried out independent audits. The Yatim Mandiri Medan Amil Zakat Institution is still not transparent in submitting financial reports, seeing that only reports on changes in funds are submitted on the official Yatim Mandiri website and magazines every month and carry out their programs very openly and transparently by placing all activities that have been carried out on the official Yatim website. Mandiri and released a magazine entitled Yatim Mandiri Inspiration for Care.